Wpływ wybranych parametrów technologicznych na przebieg i skuteczność procesu koagulacji w oczyszczaniu wód podziemnych = The influence of selected technological parameters on the course and effectiveness of coagulation in graund water treatment - Krupińska, Izabela; Konkol, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article shows and discusses the results of research concerning influence of chosen technological characteristics of the coagulation process on the efficiency of aluminum coagulants: sulfate (VI) aluminum and polyaluminum chloride (Flokor 1,2A) and also iron coagulant: sulfate (VI) iron (III): PIX-112, in the removal of underground water pollution.
Keywords: woda podziemna; substancje organiczne; koagulacja; temperatura oczyszczanej wody; czas i intensywność mieszania fazy flokulacji; underground water; organic substances; coagulant; temperature of the treated water; time and speed of mixing during the flocculation stage